ASSESSMENT OF HEAVY METAL CONTAMINATION IN WATER AROUND INDUSTRIAL LAYOUT, SAGAMU, OGUN STATE, NIGERIA - Faleye, Bamidele Ruth; Ajibade, O. M.; Babatunde, O. E.; Erharhaghen, S. E. (FUDMA JOURNAL OF SCIENCES, 2024)
Waste from industrial activities has a great impact on water quality thereby limiting water usability for domestic purposes. This study assessed the heavy metal contamination in water around the industrial layout in Sagamu, Ogun State, Nigeria. Seven (7) water samples were collected and analyzed for their physicochemical and geochemical properties using inductively coupled plasma mass spectrometry (ICP-MS). Water facie was determined using a Piper plot. Geo-Accumulation Index (Igeo), Contamination factor (Cf), Contamination degree (Cd), Quantification of Contamination (QoC) and Hazard Index (HI) of the heavy metals in water samples were obtained. Results show the ranges of physicochemical properties as, pH (4.1 - 5.9), total dissolved solid (78 - 292 ppm), electrical conductivity (0.1 - 0.4 µS/cm) and temperature (30.1 - 32.2°C). The concentration of metals in groundwater samples were obtained as Cd (0.001 - 0.004ppm,), As (00007 - 0.0011ppm), Cr (0.005-.01ppm), Pb (0.0003- 0.046ppm), Zn (0.0204-0.26ppm), Fe (0.000005- 0.013ppm), Mn (0.0009-2.5ppm) and Ni (0.001-0.03ppm). Igeo for heavy metals < 5, Fe has Cf of F>6 (strongly polluted) and Cd>32. Fe and Mn have positive QoC values indicating anthropogenic sources. Results show the HI to be greater than 1 indicating children and adults are at low risk of non-carcinogenic health problems. Water in the study area was contaminated with Pb and Mn thereby reducing its quality and exposure through derma and ingestion can cause adverse health effects. Proper sanitation with contamination control and monitoring strategies should be adopted to safeguard the health of water consumers from the study area.